Clinical Benefits of Combining Different Visualization Modalities in Neurosurgery - Schebesch, Karl-Michael; Rosengarth, Katharina; Brawanski, Alexander; Proescholdt, Martin; Wendl, Christina; Höhne, Julius; Ott, Christian; Lamecker, Hans; Doenitz, Christian (Frontiers in Surgery, 2019)
The prevailing philosophy in oncologic neurosurgery, has shifted from maximally invasive resection to the preservation of neurologic function. The foundation of safe surgery is the multifaceted visualization of the target region and the surrounding eloquent tissue. Recent advancements in preoperative and intraoperative visualization modalities have changed the face of modern neurosurgery. Metabolic and functional data can be integrated into intraoperative guidance software, and fluorescent dyes under dedicated filters can potentially visualize patterns of blood flow and better define tumor borders or isolated tumor foci. High definition endoscopes enable the depiction of tiny vessels and tumor extension to the ventricles or skull base. Fluorescein sodium-based confocal endomicroscopy, which is under scientific evaluation, may further enhance the neurosurgical armamentarium. We aim to present our institutional workup of combining different neuroimaging modalities for surgical neuro-oncological procedures. This institutional algorithm (IA) was the basis of the recent publication by Haj et al. describing outcome and survival data of consecutive patients with high grade glioma (HGG) before and after the introduction of our Neuro-Oncology Center.